2017
DOI: 10.1177/1933719116671001
|View full text |Cite
|
Sign up to set email alerts
|

Variable Methylation Potential in Preterm Placenta: Implication for Epigenetic Programming of the Offspring

Abstract: Children born preterm are reported to be at increased risk of developing noncommunicable diseases in later life. Altered placental DNA methylation patterns are implicated in fetal programming of adult diseases. Our earlier animal studies focus on micronutrients (folic acid, vitamin B) and long-chain polyunsaturated fatty acids (LCPUFAs) that interact in the 1 carbon cycle, thereby influencing methylation reactions. Our previous studies in women delivering preterm show altered plasma levels of micronutrients an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…Recent studies investigating the role of LCPUFAs in determining gestational outcomes and influencing the offspring’s health have shown that inadequate intakes during pregnancy may result in aberrant DNA methylation patterns, affecting the expression of clinically relevant genes (e.g., angiogenic factor genes) ( 32 ). This can contribute not only to the vascular dysregulation associated with abnormal placentation but might also play detrimental effects on fetal programming, ensuing in an increased long-term risk of cardiovascular diseases ( 33 ).…”
Section: Effect Of Maternal Nutrition On Pregnancy Epigenetics and Fementioning
confidence: 99%
“…Recent studies investigating the role of LCPUFAs in determining gestational outcomes and influencing the offspring’s health have shown that inadequate intakes during pregnancy may result in aberrant DNA methylation patterns, affecting the expression of clinically relevant genes (e.g., angiogenic factor genes) ( 32 ). This can contribute not only to the vascular dysregulation associated with abnormal placentation but might also play detrimental effects on fetal programming, ensuing in an increased long-term risk of cardiovascular diseases ( 33 ).…”
Section: Effect Of Maternal Nutrition On Pregnancy Epigenetics and Fementioning
confidence: 99%
“…Altogether, these candidate-based methylation studies show that mapping placental epigenome modifications attributable to air pollution offers a unique opportunity to unravel biomolecular signatures playing a potential role in the mediation of air pollution influence on postnatal life [51].…”
Section: Air Pollution-induced Placental Epigenetic Alterationsmentioning
confidence: 99%
“…As for lipids, recent studies have shown that the inadequate intake of long-chain polyunsaturated fatty acids (LCPUFA) during pregnancy may provoke aberrant DNA methylation patterns affecting clinically relevant gene expression, such as angiogenic factor genes [52,53]. This may not only contribute to vascular deregulation associated with abnormal placentation but may also have harmful effects on fetal programming, resulting in an enhanced risk of cardiovascular disease in adulthood [54]. Specific components of the Mediterranean diet assessed by the PREDIMED study, specifically omega-3 fatty acids from extra-virgin olive oil and nuts, induce methylation changes in peripheral white blood cells associated with intermediate metabolism, diabetes, inflammation and signal transduction [55].…”
Section: Macronutrientsmentioning
confidence: 99%